PENTINGNYA INTEGRITAS, INDEPENDENSI DAN PROFESIONALISME PADA KUALITAS AUDIT: THE IMPORTANCE OF INTEGRITY, INDEPENDENCE AND PROFESSIONALISM IN AUDIT QUALITY - Putri, Atika Asadita Sarni; Putri, Adriyanti Agustina; Marlina, Evi (Universitas Riau, 2024)
This research was conducted to determine the effect of integrity, independence and professionalism on audit quality of the auditors of the Financial and Development Supervisory Board of Riau Province. This research is a quantitative. The population in this study were all auditors at BPKP Riau Province, totaling 84 auditors. Sampling used the saturated sample method or total sampling so that the entire population, totaling 84 auditors at the Riau Province BPKP Representative, will be used as the research sample. The data in this study used primary data, with data collection methods using questionnaires. Analyses of multiple linear regression by using SPSS for Windows. The results of the study show that integrity, independence and professionalism affect audit quality